2017
DOI: 10.1016/j.jmb.2017.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate promotes SSB protein–protein Interactions via intrinsically disordered regions

Abstract: E. coli single strand (ss) DNA binding protein (SSB) is an essential protein that binds to ssDNA intermediates formed during genome maintenance. SSB homotetramers bind ssDNA in several modes that differ in occluded site size and cooperativity. High “unlimited” cooperativity is associated with the 35 site size ((SSB)35) mode at low [NaCl], whereas the 65 site size ((SSB)65) mode formed at higher [NaCl] (> 200 mM), where ssDNA wraps completely around the tetramer, displays “limited” cooperativity forming dimers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
97
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(107 citation statements)
references
References 66 publications
8
97
0
2
Order By: Relevance
“…Previous studies suggested that the IDLs of adjacent SSB molecules can interact with each other to enhance the cooperativity of ssDNA binding, while the IDL was also proposed to interact with the OB fold Kozlov et al, 2015Kozlov et al, , 2017. Moreover, the central role played by similar low-sequence-complexity, Gln/Gly/Pro-rich IDRs in previously investigated LLPS systems (Bakthavachalu et al, 2018;Mannen et al, 2016;Milovanovic et al, 2018;Sabari et al, 2018) as well as the predicted LLPS propensities suggest a role for the IDL in SSB LLPS ( Fig.…”
Section: Multivalent Interactions Between Ssb Idl Regions Are Requirementioning
confidence: 73%
“…Previous studies suggested that the IDLs of adjacent SSB molecules can interact with each other to enhance the cooperativity of ssDNA binding, while the IDL was also proposed to interact with the OB fold Kozlov et al, 2015Kozlov et al, , 2017. Moreover, the central role played by similar low-sequence-complexity, Gln/Gly/Pro-rich IDRs in previously investigated LLPS systems (Bakthavachalu et al, 2018;Mannen et al, 2016;Milovanovic et al, 2018;Sabari et al, 2018) as well as the predicted LLPS propensities suggest a role for the IDL in SSB LLPS ( Fig.…”
Section: Multivalent Interactions Between Ssb Idl Regions Are Requirementioning
confidence: 73%
“…The N-terminal OB domain mediates both inter-protein interactions to form tetramers (which is referred to as EcSSB henceforth), as well as high-affinity DNA binding. EcSSB was shown to exhibit high cooperativity in certain ssDNA binding conformations, which is eliminated by truncating or replacing the IDL or TIP, as well as by mutating the "bridge interface" that links adjacent SSB tetramers through an evolutionarily conserved surface near the ssDNA-binding site (2,6,8,12,18,(20)(21)(22). EcSSB can bind ssDNA with multiple conformations that wrap the ssDNA substrates to different degrees (8,(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…Recent single molecule analyses have greatly enhanced the understanding of the binding dynamics of these distinct modes (18,20). These studies have revealed the dynamic equilibrium between well-defined EcSSB functional and structural states (29), and the ability of the tetramer to diffuse quickly along the ssDNA substrate while maintaining its wrapped conformation (30).…”
Section: Introductionmentioning
confidence: 99%
“…Under low‐salt conditions (<20 m M NaCl, <1 m M MgCl 2 ), the (SSB) 35 mode is a highly cooperative binding mode in which SSB tetramers are clustered on ssDNA. However, highly cooperative binding of E. coli SSB to DNA also occurs at physiological salt and glutamate concentrations …”
Section: Single‐stranded Dna‐binding Proteinmentioning
confidence: 99%
“…However, highly cooperative binding of E. coli SSB to DNA also occurs at physiological salt and glutamate concentrations. 51 The structure of E. coli SSB in complex with dC 35 polymers revealed a "baseball seam" topology of the DNA [ Fig. 4(b)].…”
Section: Single-stranded Dna-binding Proteinmentioning
confidence: 99%